PENGARUH EFISIENSI MODAL KERJA, LIKUIDITAS, DAN SOLVABILITAS TERHADAP PROFITABILITAS (Studi Pada Perusahaan Farmasi yang Terdaftar di BEI Periode 2007-2011) - Sartika, Farahiyah; Herawati, Juni (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to determine the effect of the  efficiency of working capital (working capital turnover), liquidity (current ratio), and solvency (debt to total assets ratio) toward profitability (return on investment) either simultaneously or partially in the pharmaceutical company listed on the Indonesian Stock Exchange over period 2007-2011. Type of research used in this research is associative research that aims to explain the relationship between two or more variables  through hypothesis testing. The sampling technique used was purposive sampling and obtained a sample of 7 companies. Data which have already collected are processed with classic assumption test before hypothesis test. To test the hypothesis proposed in this study  used multiple regression analysis.   The results of the research  simultaneously  using F test  showed  that  all  of  the three  independent  variables  have a significant effect  on profitability  (return on investment). The results of the research partially using t test showed that  liquidity  (current ratio)  have positive significant influence on  profitability  (return on investment). While the efficiency of working capital (working capital turnover) and solvency (debt to  total  assets ratio)  have no significant influence  on profitability  (return on investment). Keywords: Profitability, Efficiency of Working Capital, Liquidity, Solvency